Permeability of rat and rabbit erythrocyte membranes for a series of amides - Gordiyenko, O.I.; Kovalenko, G.V.; Kovalenko, I.F.; Kholodnyy, V.S.; Linnik, T.P.; Gordiyenko, E.O. (Elsevier B.V., 2008)
Permeability coefficients of rat and rabbit erythrocyte membranes for a series of amides, as well as for erythrocytes treated with p-chloromercuribenzenesulfonic acid monosodium salt (pCMBS) have been determined at 25 and 37 °C. Directly proportional dependence of the pCMBS treated erythrocyte permeability for investigated substances and their partition coefficients between the hydrophobic phase and water as well as the values of activation energy of this process indicate that penetration of small hydrophilic molecules is realized by passive diffusion through the lipid bilayer. The results obtained indicate that penetration of small hydrophilic molecules of formamide through lipids is determined by the existence of a free space between hydrocarbon chains that arises from kink formation. The differences in permeability between rat and rabbit erythrocyte membranes could arise in particular as a result of the differences in lipid composition.
Keywords: Erythrocyte; Permeability; Amides